Marine protected areas and fisheries restricted areas in the Mediterranean: assessing "actual" marine biodiversity protection coverage at multiple scales. (February 2016) - Rodríguez-Rodríguez, David; Rodríguez, J.; Abdul Malak, D.; Nastasi, A.; Hernández, P.
Abstract: This study uses a tiered approach to assessing progress towards achieving the Convention on Biological Diversity (CBD) target to increase marine protected area (MPA) coverage to 10% at different scales: the whole Mediterranean Sea, by ecoregions and by countries. It additively considers marine protection coverage by conventional MPAs (cMPAs; tier 1); unconventional MPAs (uMPAs, including international Fisheries Restricted Areas – iFRAs-; tier 2); and Other Effective Area-Based Conservation Measures (OEABCMs, including national FRAs–nFRAs; tier 3). It also discusses the appropriateness of considering tiers 2 and 3 as legal and managerial tools for sustainable marine development in national reporting against international protection coverage targets. At the Mediterranean Sea scale, by mid-2015 there were 1077 cMPAs which covered 6.45% of its area. At the ecoregional scale, only the Western Mediterranean ecoregion exceeds the 10% coverage target. At national scale, four countries (Monaco, France, Spain and Turkey) currently exceed the 10% target for their entire hypothetical Exclusive Economic Zones (EEZs). The cMPA designations that contribute most to Mediterranean MPA coverage are Specially Protected Areas of Mediterranean Importance (SPAMIs), the Pelagos Sanctuary, Natura 2000 sites and national designations, respectively. When considering uMPAs, the amount of marine area under protection in the Mediterranean reaches 1, 632, 507 km 2 or roughly 64.48% of the Mediterranean Sea area; all the ecoregions more than double the CBD coverage target; all countries but Malta meet the target in their inshore waters; and all countries meet the target in their whole hypothetical EEZs. Finally, nFRAs contributed 565 km 2 of additional protected area and made the percentage of legally protected marine area reach 64.50% of the total Mediterranean Sea area. Highlights: A multi-scale approach to assessing Aichi Target 11 in the Mediterranean was used. Conventional MPAs, unconventional MPAs and fisheries restricted areas were considered. 6.45% of the Mediterranean Sea was covered by conventional MPAs by mid-2015. 64.50% of the Mediterranean is legally protected by any of the protection measures. Legal MPA coverage in the Mediterranean Sea is one of the world's highest.